2009
DOI: 10.1080/09668130902753275
|View full text |Cite
|
Sign up to set email alerts
|

Oil and Gas: A Blessing for the Few. Hydrocarbons and Inequality within Regions in Russia

Abstract: Building on earlier work on regional inequality in Russia the article seeks to demonstrate that the regional oil and gas abundance is associated with high within-region inequality. It provides empirical evidence that hydrocarbons represent one of the leading determinants of an increased gap between rich and poor in the producing regions. The discussion focuses on a possible cluster of geographic, economic and political factors underlying the phenomenon. In this article, we investigate the hypothesis that growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 42 publications
2
28
0
7
Order By: Relevance
“…For Mexico, López-Feldman et al (2007) documented increased resource income somewhat lowering inequality and poverty, but resource income was itself unequally distributed. For Russia, Buccellato and Mickiewicz (2009) showed that oil and gas abundance led to local level inequality. Caselli and Michaels (2009) found that oil may have reduced poverty in Brazil, but the results were not robust.…”
Section: Introductionmentioning
confidence: 99%
“…For Mexico, López-Feldman et al (2007) documented increased resource income somewhat lowering inequality and poverty, but resource income was itself unequally distributed. For Russia, Buccellato and Mickiewicz (2009) showed that oil and gas abundance led to local level inequality. Caselli and Michaels (2009) found that oil may have reduced poverty in Brazil, but the results were not robust.…”
Section: Introductionmentioning
confidence: 99%
“…Angrist and Kugler (2008) find that dependence on coca production and associated rent-seeking explains differences in the extent of civil conflict across Colombian regions. Withinregion income inequality can also be associated with regional oil and gas abundance (see the empirical analysis across Russian regions by Buccellato and Mickiewitz, 2009). Deaton and Niman (2012) make use of county data from the Appalachian region to show how mineral dependence increases poverty rates in the longer term (although it tends to have the opposite effect in the short term).…”
Section: Other Variablesmentioning
confidence: 99%
“…As a result, large, politically connected enterprises dominate Russia's business landscape. Moreover, the lack of universal property rights is reflected by the uneven distribution of income, and Russia is plagued by some of the most extreme social differences and pockets of dire poverty (Glaeser et al 2003;Gerry et al 2008;Buccellato and Mickiewicz 2009).…”
Section: Entrepreneurship In Russiamentioning
confidence: 99%